Los difusos contornos para distinguir la desobediencia a la autoridad como delito y como infracción administrativa: mandato de tipificación, libertad ambulatoria y mínima intervención - José Ignacio Cubero Marcos (Revista Vasca de Administración Pública)
The Criminal Code and the 4/2015 Organic Law regulating the protection of the citizens security have criminalised disobedience as an illegal act. People need to know what conduct constitutes a criminal offence and what is considered an administrative offence. It is even worth considering whether, from the legislator¿s perspective, criminal policy makes it advisable to decriminalise it, making it an administrative offence. To all this, three issues should be added: the deficient criminalisation to distinguish between the two offences, which has forced the jurisprudence to make a pronouncement; two, the legal consequences that the flagrant and immediate commission of disobedience entails for the freedom of movement of the perpetrator. It should be borne in mind that an individual can be arrested at the very moment when the typical conduct is carried out, which happened on many occasions during the state of alarm. Finally, the legislator should consider decriminalising disobedience in accordance with the principle of minimum intervention and the last resort of criminal law.